Plant seedlings of peas, tomatoes, and cucumbers exude compounds that are needed for growth and chemoattraction of Rhizobium leguminosarum bv. viciae 3841 and Azospirillum brasilense Sp7 - Nisha, Fatema A.; Tagoe, Janice N.A.; Pease, Amanda B.; Horne, Shelley M.; Ugrinov, Angel; Geddes, Barney A.; Prüß, Birgit M. (Canadian journal of microbiology, 2024)
This study characterizes seedling exudates of peas, tomatoes, and cucumbers at the level of chemical composition and functionality. A plant experiment confirmed that Rhizobium leguminosarum bv. viciae 3841 enhanced growth of pea shoots, while Azospirillum brasilense Sp7 supported growth of pea, tomato, and cucumber roots. Chemical analysis of exudates after 1 day of seedling incubation in water yielded differences between the exudates of the three plants. Most remarkably, cucumber seedling exudate did not contain detectable sugars. All exudates contained amino acids, nucleobases/nucleosides, and organic acids, among other compounds. Cucumber seedling exudate contained reduced glutathione. Migration on semi solid agar plates containing individual exudate compounds as putative chemoattractants revealed that R. leguminosarum bv. viciae was more selective than A. brasilense, which migrated towards any of the compounds tested. Migration on semi solid agar plates containing 1:1 dilutions of seedling exudate was observed for each of the combinations of bacteria and exudates tested. Likewise, R. leguminosarum bv. viciae and A. brasilense grew on each of the three seedling exudates, though at varying growth rates. We conclude that the seedling exudates of peas, tomatoes, and cucumbers contain everything that is needed for their symbiotic bacteria to migrate and grow on.